2021
DOI: 10.3892/etm.2021.10679
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of LINC01385 inhibits osteoarthritis progression by modulating the microRNA‑140‑3p/TLR4 axis

Abstract: Long non-coding (lnc) RNAs have been associated with osteoarthritis (OA) progression. The aim of the present study was to investigate the regulatory mechanism of lncRNA LINC01385 in OA in vitro. The mRNA expression level of LINC01385, microRNA(miR)-140-3p, and Toll-like receptor 4 (TLR4) was detected using reverse transcription-quantitative PCR, while ELISA was used to determine the concentration of different inflammatory factors [tumor necrosis factor-α (TNF-α), IL-6, and prostaglandin E 2 (PGE 2 )]. The viab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 31 publications
(55 reference statements)
0
7
0
Order By: Relevance
“…To moreover check on the circKMT2E/miR-140-5p/TLR4 regulatory pathway, our research team performed a dual-luciferase reporter assessment to confirm the combinative connection between circKMT2E and miR-140-5p, they used transfected cells to verify the ability of circKMT2E to promote apoptosis. Wang et al [ 21 ] previously found that knockdown of LINC01385 can inhibit the progression of OA on the basis of adjusting the microRNA-140-3p/TLR4 axis. Thus, it can be deduced that upregulated circKMT2E in chondrocytes with OA may be involved in the apoptosis of chondrocytes by targeting TLR4 via the sponge function to miR-140-5p.…”
Section: Discussionmentioning
confidence: 99%
“…To moreover check on the circKMT2E/miR-140-5p/TLR4 regulatory pathway, our research team performed a dual-luciferase reporter assessment to confirm the combinative connection between circKMT2E and miR-140-5p, they used transfected cells to verify the ability of circKMT2E to promote apoptosis. Wang et al [ 21 ] previously found that knockdown of LINC01385 can inhibit the progression of OA on the basis of adjusting the microRNA-140-3p/TLR4 axis. Thus, it can be deduced that upregulated circKMT2E in chondrocytes with OA may be involved in the apoptosis of chondrocytes by targeting TLR4 via the sponge function to miR-140-5p.…”
Section: Discussionmentioning
confidence: 99%
“…In both tuberculosis and carciogenesis, Il‐6 play an important role again [68, 69]. Regarding the miR‐140‐3p, it is evident that this miRNA is also significantly down‐regulated in human chondrocytes in glenohumeral arthritis [70], among others. MiR‐140‐3p was shown to reduce the concentration of interleukin‐1ß (IL‐1ß) induced inflammatory factors [70].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the miR‐140‐3p, it is evident that this miRNA is also significantly down‐regulated in human chondrocytes in glenohumeral arthritis [70], among others. MiR‐140‐3p was shown to reduce the concentration of interleukin‐1ß (IL‐1ß) induced inflammatory factors [70]. IL1‐ß plays a crucial role mainly in the inflammatory phase of tendon healing [71], but it has also been shown that it has a significant role in arthritis [72].…”
Section: Discussionmentioning
confidence: 99%
“…Circular RNA S-phase cyclin A associated protein in the endoplasmic reticulum (circSCAPER) is highly expressed in IL-1β-treated chondrocytes and OA cartilage and has been reported to act as a “sponge” of miR-140-3p ( 78 ). miR-140 was also shown to be the target of long non-coding RNAs LINC01385 ( 79 ) and plasmacytoma variant translocation 1 (PVT1) ( 80 ). Restoration of miR-140 is being tested as a therapeutic approach in preclinical models of OA.…”
Section: Osteoarthritismentioning
confidence: 99%